2022
DOI: 10.1155/2022/3698772
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mechanism of Realgar against Esophageal Cancer Based on Ferroptosis Induced by ROS-ASK1-p38 MAPK Signaling Pathway

Abstract: Background. Realgar (REA), a Chinese herbal decoction, has been used to treat various tumors and has produced positive outcomes; however, there is a lack of convincing evidence for the treatment of esophageal cancer. The present study aimed to investigate the effects of REA on esophageal cancer (EC) and explore its mechanism. Methods. EC cells Eca109 and KYSE150 were selected for this study, and different groups of treated cells were set up. We studied the inhibition rate and half inhibition concentration (IC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…[32] Realgar also exhibits strong activity in inducing cell cycle arrest, [34] and interruption of realgar-induced G2/M progression is initiated through the activated Gadd45A/Cdc2/ cyclin B pathway, [33] leading to reduced migration and invasion of tumor cells. [36] Further investigations have revealed that realgar can inhibit the activation of the ROS-recombinant apoptosis signal regulating kinase 1-p38 mitogen-activated protein kinase signaling pathway [37] and decrease the expression of MMP-2 and MMP-9. [38] thus inhibiting the proliferation and neovascularization of tumor cells.…”
Section: Protective Effects On the Central Nervous Systemmentioning
confidence: 99%
“…[32] Realgar also exhibits strong activity in inducing cell cycle arrest, [34] and interruption of realgar-induced G2/M progression is initiated through the activated Gadd45A/Cdc2/ cyclin B pathway, [33] leading to reduced migration and invasion of tumor cells. [36] Further investigations have revealed that realgar can inhibit the activation of the ROS-recombinant apoptosis signal regulating kinase 1-p38 mitogen-activated protein kinase signaling pathway [37] and decrease the expression of MMP-2 and MMP-9. [38] thus inhibiting the proliferation and neovascularization of tumor cells.…”
Section: Protective Effects On the Central Nervous Systemmentioning
confidence: 99%
“…This finding suggests the potential of gliotoxin as a novel natural therapy for ESCC 232 . In addition, realgar (REA) , a Chinese herbal decoction, was found to not only decrease the proliferation, migration and invasion of KYSE150 and Eca109 cells but also promote ferroptosis by activating the ROS-ASK1-p38 MAPK signaling pathway 233 . Moreover, high expression of NRF2 protein in both primary tissues and EAC cell lines was detected by Ballout et al , and further studies showed that treatment with the NRF2 inhibitor brusatol alone or in combination with cisplatin induced ferroptosis of EAC cells by targeting NRF2; these results were evidenced by reduced expression of the ferroptosis markers GPX4 and xCT, which was confirmed in vivo 234 .…”
Section: Targeting Ferroptosis Pathways With Small-molecule Compounds...mentioning
confidence: 99%